Feasibility and Impact of a Combined Supervised Exercise and Nutritional-Behavioral Intervention following Bariatric Surgery: A Pilot Study. (23rd June 2015) - Jassil, Friedrich C.; Manning, Sean; Lewis, Neville; Steinmo, Siri; Kingett, Helen; Lough, Fiona; Pucci, Andrea B. F.; Cheung, W. H.; Finer, Nicholas; Walker, Judith; Doyle, Jaqueline; Batterham, Rachel L.
Abstract : Background. Lifestyle intervention programs after bariatric surgery have been suggested to maximise health outcomes. This pilot study aimed to investigate the feasibility and impact of an 8-week combined supervised exercise with nutritional-behavioral intervention following Roux-en-Y gastric bypass and sleeve gastrectomy. Methods. Eight female patients (44 ± 8 years old, BMI = 38.5 ± 7.2 kgm −2 ) completed the program. Before and after intervention, anthropometric measures, six-minute walk test (6MWT), physical activity level, eating behavior, and quality of life (QoL) were assessed. Percentage weight loss (%WL) outcomes were compared with a historical matched control group. Results. The program significantly improved functional capacity (mean increment in 6MWT was 127 ± 107 meters, p = 0.043 ), increased strenuous intensity exercise (44 ± 49 min/week, p = 0.043 ), increased consumption of fruits and vegetables (p = 0.034 ), reduced consumption of ready meals (p = 0.034 ), and improved "Change in Health" in QoL domain (p = 0.039 ). The intervention group exhibited greater %WL in the 3–12-month postsurgery period compared to historical controls, 12.2 ± 7.5% versus 5.1 ± 5.4%, respectively (p = 0.027 ). Conclusions. Lifestyle intervention program following bariatric surgery is feasible and resulted in several beneficial outcomes. A large randomised control trial is now warranted.